2013
DOI: 10.1111/aor.12186
|View full text |Cite
|
Sign up to set email alerts
|

Effective Use of Alteplase for Occluded Tunneled Venous Catheter in Hemodialysis Patients

Abstract: Despite their propensity for significant infectious and mechanical complications, tunneled central venous catheters (CVCs) have become a common means of vascular access in the world for patients requiring chronic hemodialysis for end-stage renal disease. The objective of this study was to explore if cryopreserved solutions of the thrombolytic agent alteplase could be used as an effective, safe, and economically reasonable alternative in hemodialysis patients with occluded tunneled CVC. Patients requiring chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 19 publications
2
20
0
1
Order By: Relevance
“…Our study showed that 87% of the 815 catheter attempts resulted in successful catheter clearance after the use of alteplase: 77% after one dose and 10% after the second dose; only 13% did not result in success. Similar results were reported by other authors in oncology and HD patients .…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that 87% of the 815 catheter attempts resulted in successful catheter clearance after the use of alteplase: 77% after one dose and 10% after the second dose; only 13% did not result in success. Similar results were reported by other authors in oncology and HD patients .…”
Section: Discussionsupporting
confidence: 93%
“…15,17,20 Clinical trials comparing unplanned HD vs. unplanned PD starts will hardly ever be carried out because of their ethical implications. Therefore, observational studies of good quality performed in developed and developing nations must be carried out to further support urgent-start PD.…”
Section: Clinical Trials On the Use Of Pd In Unplanned Dialysis Startsmentioning
confidence: 99%
“…13,14 PeritoneAl diAlysis As the method of choice to urgently stArt therAPy Unplanned start dialysis, also known as urgent-start dialysis, may be defined as the initiation of HD without a definitive functioning vascular access -i.e., treatment is started with a CVC -or the start of PD within seven days of the implantation of a catheter. 15,16,17 Iversen et al 15 retrospectively reviewed the Danish Nephrology Registry (2008)(2009)(2010)(2011) and reported that 50% of the incident patients on RRT had unplanned therapy starts. In Brazil, approximately 60% of the incident patients on RRT do not have a definitive access and are treated with a CVC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Unplanned dialysis may be defined as the start of HD without a functioning definitive vascular access (AVF), i.e., using a CVC, or as the start of PD within less than 7 days after its implantation. [12][13][14] Ivarsen et al 12 retrospectively reviewed the Danish Nephrology Registration from 2008 to 2011 and found that 50% of incident patients on RRT started it in an unplanned manner. In Brazil, approximately 60% of incident patients on RRT have no definitive access and need to be treated through CVC.…”
mentioning
confidence: 99%